Integrating public affairs information strategy with organizational practices in healthcare delivery organizations. Issue 4 (17th May 2018) - Vamstad, Brian S.; Gordon, Mark
Abstract : To develop and implement policy, lawmakers rely on the input from external experts and stakeholders. Public affairs professionals are responsible for monitoring the sociopolitical environment and responding to public policy proposals on behalf of firms and organizations. However, how public affairs operate intraorganizationally and develop information strategies is not clear nor consistent in the literature. The purpose was to explore how public affairs engage with internal stakeholders to leverage their knowledge for information strategies in responding to policymakers. Knowledge transfer served as a theoretical framework through a qualitative multiple case study of 3 not‐for‐profit healthcare delivery organizations. Primary data were collected using semistructured interviews from public affairs ( n  = 11) and healthcare professionals ( n  = 18) along with a review of organizational documents and public records. Patterns and themes emerged through cross‐case synthesis, presented as a process‐based model and theory. Public affairs structures and decision‐making processes varied across cases indicating no coherent approach by practitioners. Intraorganizational engagement and knowledge transfer processes were managed both consistently and ad hoc, through informal and formal methods. Practitioner strategies and tactics were identified to facilitate internal interaction such as filtering policy issues and effective communication methods. Common institutional barriers were identified that made stakeholder engagement a challenge. This study provides insight into understanding how public affairs practice internally and supports the fundamental importance of linking knowledge into public policymaking.